B₁₂P₂: improved epitaxial growth and evaluation of α irradiation on its electrical transport properties - Frye, Clint D. (Kansas State University, 2016)
The wide bandgap (3.35 eV) semiconductor icosahedral boron phosphide (B₁₂P₂) has been reported to self-heal from radiation damage from β particles (electrons) with energies up to 400 keV by demonstrating no lattice damage using transmission electron microscopy. This property could be exploited to create radioisotope batteries–semiconductor devices that directly convert the decay energy from a radioisotope to electricity. Such devices potentially have enormous power densities and decades-long lifetimes. To date, the radiation hardness of B₁₂P₂ has not been characterized by electrical measurements nor have B₁₂P₂ radioisotope batteries been realized. Therefore, this study was undertaken to evaluate the radiation hardness of B₁₂P₂ after improving its epitaxial growth, developing ohmic electrical contacts, and reducing the residual impurities. Subsequently, the effects of radiation from a radioisotope on the electrical transport properties of B₁₂P₂ were tested. B₁₂P₂ was grown epitaxially on 4H-SiC by chemical vapor deposition (CVD) over the temperature range of 1250-1450 °C using B₂H₆ and PH₃ precursor gases in a H₂ carrier gas. The epitaxial relationship between B₁₂P₂ and 4H-SiC was (0001)B₁₂P₂[1100]B₁₂P₂

(0001)4H-SiC[1100]4H-SiC using hexagonal indices (or (111)B₁₂P₂[121]B₁₂P₂

(0001)4H-SiC[1100]4H-SiC using rhombohedral indices for B₁₂P₂). X-ray diffraction (XRD) rocking curve measurements (assessing the crystal quality) about the B₁₂P₂ (0003) peak were minimized at 1300 °C indicating it was the optimum growth temperature studied. By miscutting the (0001) 4H-SiC substrate 4° to the (1100) plane, B₁₂P₂ rotational twinning, a type of crystal defect, was strongly suppressed to a twin density of <1% in comparison to a standard miscut to the (1120) plane which resulted in a twin density of 30%. Cr/Pt (500/1000 Å) and Ni/Au (1000/1000 Å) ohmic contacts to B₁₂P₂ were developed. Ni/Au contacts annealed at 500 °C for 30 s in Ar proved to be the best contact studied with a specific contact resistance of 3x10⁻⁴ Ω-cm². Background impurities were measured by secondary ion mass spectrometry (SIMS), and Si (≈1x10¹⁹-5x10¹⁹ cm⁻³), C (≈5×10¹⁹-2x10²⁰ cm⁻³), and O (≈2×10²⁰ cm⁻³) were the primary residual impurities when B₁₂P₂ was grown on 4H-SiC at 1250 °C. The SiC substrate caused Si and C contamination, and the TaC-coated graphite heating element was a second C source. Since Si and C are p-type dopants in B₁₂P₂ (confirmed by Hall Effect measurements), the 4H-SiC substrate was exchanged with AlN/sapphire, and the TaC-coated graphite susceptor was replaced with Zr metal. With the new substrate and susceptor, the Si and C concentrations were decreased to 2-3x10¹⁸ cm⁻³ and 4x10¹⁸ cm⁻³, respectively. The radiation hardness of p-B₁₂P₂ grown on AlN/sapphire was compared to an epi-layer of p-4H-SiC (a conventional radiation hard material) by temperature-dependent Hall Effect measurements. A defect band was present in B₁₂P₂ prior to irradiation, and radiation further contributed to defect band conduction and lowered the hole mobility. Evidence for self-healing of B₁₂P₂ from electrical measurements remains inconclusive. However, the steps necessary to evaluate B₁₂P₂ for device applications has been clarified, and includes further reductions in crystalline defects and residual impurities, especially carbon and oxygen. This work was performed under the auspices of the U.S. Department of Energy by Lawrence Livermore National Laboratory under Contract DE-AC52-07NA27344, LLNLABS- 706086.
Keywords: Materials science; Chemical enginneering